Critical factors influencing Firms' risk-taking behaviour: CEO characteristics and the moderating role of the audit committee - Arulanandam, Benedict Valentine*; Selvan, Christo; Goh, Xin Tong (Prague University of Economics and Business, 2023)
This paper aims to explore the effects of Chief Executive Officer (CEO) characteristics on managerial risk-taking behaviour and the moderating impact of Audit Committee (AC) ownership and ethnicity in this relationship. The underlining theory employed in this study is the Upper Echelons Theory (UET). Data were hand-collected from annual reports of the top 100 Malaysian PLCs over 2015-2020 and were analysed through multiple regression analysis and Hayes’ Process moderation analysis. The findings suggest that CEO age negatively affects risk-taking. The results, however, do not support the use of CEO tenure and gender as proxies for managerial risk-taking behaviour. AC ownership has a significant positive moderating effect on the relationship between CEO age, tenure, gender and risk-taking. Contrarily, AC ethnicity only significantly moderates the association between CEO gender and risk-taking. This study further adds to the existing literature considering these independent variables. Implications for Central European audience: This study serves as a good yardstick for exploring the effects of CEOs’ characteristics. While this study is within the Malaysian context, it is undoubtedly useful within the Central European context. The risk-taking behaviour can be dispersed over all sectors, especially when this study employs the UET theory. The findings would set a comparison for those corporates in Central European countries.